2022
DOI: 10.3390/ijerph192215104
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Network of Stress, Coping and Social Support in an Aboriginal Population

Abstract: Over the past decades, increasing research interest has been directed towards the psychosocial factors that impact Aboriginal health, including stress, coping and social support. However, there has been no study that examined whether the behaviours, cognitions and emotions related to stress, coping and social support constitute a psychological network in an Aboriginal population and that examined its properties. To address this gap, the current study employed a new methodology, network psychometrics, to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 97 publications
1
1
0
Order By: Relevance
“…Another noteworthy finding is that family eating behavior was related to the family APGAR index and negatively to family food rules. This finding was consistent with a previous report on parents in the United States, which showed parent report of frequent family meals was associated with higher levels of family functioning and was unrelated to other indicators of parent body size ( 32 ). Besides, research has demonstrated a link between the frequency of family meals and greater fruit and vegetable consumption (family food accessibility) ( 34 ), which is inconsistent with results from this study among Chinese parents of adolescents who are overweight or obese.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Another noteworthy finding is that family eating behavior was related to the family APGAR index and negatively to family food rules. This finding was consistent with a previous report on parents in the United States, which showed parent report of frequent family meals was associated with higher levels of family functioning and was unrelated to other indicators of parent body size ( 32 ). Besides, research has demonstrated a link between the frequency of family meals and greater fruit and vegetable consumption (family food accessibility) ( 34 ), which is inconsistent with results from this study among Chinese parents of adolescents who are overweight or obese.…”
Section: Discussionsupporting
confidence: 92%
“…Findings suggested that family-related variables constituted a connected network in adolescents with overweight or obesity. The presence of at least one path between every node of the network indicated that family features variables in the adolescent with overweight or obesity form a connected network ( 32 ). The communities of the family food environment, parental rearing styles, family APGAR index, and parental educational attainment could have been completely isolated from one another.…”
Section: Discussionmentioning
confidence: 99%